Engineering of a jointed shoe last for quantifying the tibiocalcaneale and medio lateral kinematics caused by different shoe geometries - Daenhardt, M.; Harig, C.; Witte, K.; Edelmann-Nusser, J.; Kälin, X. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The influence of different shoe geometries on medio-lateral foot movement was studied by a mechanical test bed. It could be found that the width of the midsole is the dominant geometry parameter which affects the angular velocity in ankle joint. In addition, the effect of varying subtalar joint axis orientations was researched by a multibody simulation (MSC.ADAMS 2005) of a simplified running step. Meaningful variations in subtalar joint kinematics could be shown.